Private practitioners`use of exercise therapy in lower back pain - Z. Strydom; M. Faure; M. M. Bester (South African Journal of Physiotherapy, 2005)
Introduction: Lower back pain (LBP) is a common problem treated by physiotherapists.  Recent research confirms the need for a more dynamic approach, to the management of this condition and includes progressive activity and exercise.  The current use of exercise therapy for people with LBP and the implementation of evidence based practice in this field in South Africa, is unknown.  As 80% of physiotherapists in South Africa offer services in private sector, the purpose of the study was to determine the use of this modality by physiotherapists.  The specific aims were to determine how many physiotherapists utilise exercise therapy, how much therapy time is spent on it and how the modality is applied.  This information can determine whether there is a need for continuing professional development in this area.